The Impairment of Methyl Metabolism From luxS Mutation of Streptococcus mutans - Hu, Xuchen; Wang, Yuxia; Gao, Li; Jiang, Wenxin; Lin, Wenzhen; Niu, Chenguang; Yuan, Keyong; Ma, Rui; Huang, Zhengwei (Frontiers in Microbiology, 2018)
Abstract The luxS gene is present in a wide range of bacteria and is involved in many cellular processes. LuxS mutation can cause autoinducer(AI)-2 deficiency and methyl metabolism disorder. The objective of this study was to demonstrate that, in addition to AI-2-mediated quorum sensing (QS), methyl metabolism plays an important role in LuxS regulation in Streptococcus mutans. The sahH gene from Pseudomonas aeruginosa was amplified and introduced into the S. mutans luxS-null strain to complement the methyl metabolism disruption in a defective QS phenotype. The intracellular activated methyl cycle (AMC) metabolites [S-adenosylmethionine (SAM), S-adenosylhomocysteine (SAH), homocysteine (HCY), and methionine] were quantified in wild-type S. mutans and its three derivatives to determine the metabolic effects of disrupting the AMC. Biofilm mass and structure, acid tolerance, acid production, exopolysaccharide synthesis of multispecies biofilms and the transcriptional level of related genes were determined. The results indicated that SAH and SAM were relatively higher in S. mutans luxS-null strain and S. mutans luxS null strain with plasmid pIB169 when cultured overnight, and HCY was significantly higher in S. mutans UA159. Consistent with the transcriptional profile, luxS deletion-mediated impairment of biofilm formation and acid tolerance was restored to wild-type levels using transgenic SahH. These results also suggest that methionine methyl metabolism contributes to LuxS regulation in S. mutans to a significant degree.